2005
DOI: 10.1021/ie050563p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotalcite as CO2 Sorbent for Sorption-Enhanced Steam Reforming of Methane

Abstract: Sorption-enhanced reforming of methane is an attractive option for the combined production of electricity and capture of CO2. In this process, the steam-reforming catalyst is mixed with a CO2 sorbent. During the reaction, CO2 is adsorbed, leading to an increase of the hydrogen production rate. Once the sorbent is saturated, it must be regenerated using purge gas, usually steam. The amount of steam needed for CO2 removal from the saturated sorbent determines the system efficiency of the process to a large exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(143 citation statements)
references
References 14 publications
2
138
0
1
Order By: Relevance
“…Indeed, it was found earlier that the presence of steam in the gas stream has a significant effect on the capacity for CO 2 . [13,32,33] Increasing the steam/CO 2 ratio facilitates a quick and efficient desorption and has a positive influence on the adsorption capacity as demonstrated recently. [33] Moreover, it is worth to test sorbents under conditions that are close to the real SEWGS application.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Indeed, it was found earlier that the presence of steam in the gas stream has a significant effect on the capacity for CO 2 . [13,32,33] Increasing the steam/CO 2 ratio facilitates a quick and efficient desorption and has a positive influence on the adsorption capacity as demonstrated recently. [33] Moreover, it is worth to test sorbents under conditions that are close to the real SEWGS application.…”
Section: Resultsmentioning
confidence: 80%
“…[10] In parallel with the bench-scale experiment, investigations on hydrotalcite and derivative materials are ongoing at the laboratory scale. Despite a few earlier studies on CO 2 sorption using hydrotalcite-based sorbents under water gas shift conditions, [8,9,[11][12][13] the true nature of the species responsible for CO 2 reversible adsorption at such temperatures is still not well understood. In particular, the present study is focused on the role of alkaline promoters which have been earlier found to significantly increase the CO 2 sorption capacity of hydrotalcites.…”
Section: Introductionmentioning
confidence: 99%
“…Ca and Mg hydrotalcite supports performed poorly, as expected given the severe temperatures of carbonation and calcinations used here. This is due to first, loss of their H 2 O interlayer up to 200°C, followed by the irreversible dehydroxylation and decarbonisation above 500°C, leaving a spinel structure (Reijers et al, 2006). Similarly, magnesite was also used outside of its optimal carbonation-calcination range, yielding a poor 3.9% capacity for CO 2 adsorption used during the test.…”
Section: Resultsmentioning
confidence: 99%
“…Among various CO 2 mesoporous adsorbents, LDH-base materials have been identified as suitable materials for CO 2 sorption at moderate temperatures (T ≤ 400 °C) [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] due to their properties such as large surface area, high anion exchange capacity (2-3 meq/g) and good thermal stability [37][38][39][40]. The LDH materials themselves do not possess any basic sites.…”
Section: Co 2 Capture By Different Alkaline and Alkaline-earth Ceramicsmentioning
confidence: 99%